2017
DOI: 10.12693/aphyspola.132.455
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Behavior of Boron-Doped AISI 1020 Steels

Abstract: In the present study, the wear properties of AISI 1020 steels produced by a casting process with different boron contents were investigated, using a pin-on-disc tribometer under dry sliding conditions. The friction coefficients of undoped AISI 1020 steel, 0.002 and 0.01 wt% boron-doped samples were 0.33, 0.27, and 0.32, respectively. The addition of boron into AISI 1020 steel led to a decrease in the friction coefficient, due to the lubricating effect of boron; X-ray diffraction showed that both Fe2B and FeB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The direction of the rippled surface was perpendicular to the sliding movement with valleys and edges. In other study, similar deformed surface was observed on the worn surface of boron dopped AISI 1020 and 205 manganese steel after sliding against high‐speed steel counterbody 58,59 …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The direction of the rippled surface was perpendicular to the sliding movement with valleys and edges. In other study, similar deformed surface was observed on the worn surface of boron dopped AISI 1020 and 205 manganese steel after sliding against high‐speed steel counterbody 58,59 …”
Section: Resultssupporting
confidence: 74%
“…In other study, similar deformed surface was observed on the worn surface of boron dopped AISI 1020 and 205 manganese steel after sliding against high-speed steel counterbody. 58,59 As discussed previously, harder Al 2 O 3 counterbody forms wear debris and flaky pieces (see Figure 9B). The formation of wear debris was attributed to the low yield strength of Al atoms present in the coating as well as in the counterbody, causing to ease in breakage during leading to three-body wear mechanism.…”
Section: Worn Surface Morphologymentioning
confidence: 51%
“…Despite the deteriorated surface roughness after the plasma nitriding process, better tribological surface properties were achieved (lower coefficient of friction µ and wear coefficient K). Similar results were achieved at work [60,61].…”
Section: Morphology and Surface Texturesupporting
confidence: 86%
“…Hence, these hard phases, such as Fe 2 B and FeB, are separated during the sliding with the applied load, and delamination finally occurs. The microcracks develop under the surface of the sample and eventually spalling occurs, owing to surface roughness and repetitive forces acting on wear debris [39,40].…”
Section: Resultsmentioning
confidence: 99%